Türkiye arkeolojik yerleşmeleri. (İstanbul İstanbul İstanbul İstanbul İstanbul İstanbul)
8 cilt (1. c. 33 s., [473] y., [35] s., 2 katlı sayfa ; 2. c. 28, [556] y., [72] s., 2 katlı sayfa ; 3. c. 22 s., [804] y., [74] s., 2 katlı sayfa ; 4,1. c. [654] s. ; 4,2. c. [458] s., 2 katlı sayfa ; 5,1. c. 27, [142] s., 3 katlı sayfa ; 7.c. 12, [196], 10, [428], 1 katlı sayfa ; 8.c. 15, [405] s., 2 katlı sayfa)